Polianthes oaxacana y P. geminiflora var. pueblensis (Agavaceae), taxa nuevos de México - García-Mendoza, Abisaí J.; Solano, Eloy (Instituto de Ecología, A.C., 2007)
Two new taxa, Polianthes oaxacana and P. geminiflora var. pueblensis, are described and illustrated. Polianthes oaxacana, from the state of Oaxaca, belongs to subgenus Bravoa and is characterized by its tubular, bilaterally symmetrical flowers, the distal part campanulate, and anthers appressed to the upper side of the perigonium limb. The new species is compared with Polianthes bicolor Solano & García-Mend., and P. mexicana Zucc.Polianthes geminiflora var. pueblensis belongs to subgenus Bravoa and is distinguished from other varieties of the species by its linear leaves with papillose or regurlarly denticulate margin and some anatomical characters.